2016
DOI: 10.1177/0961203315622817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a one-year physical activity programme for women with systemic lupus erythematosus – a randomized controlled study

Abstract: Physical activity and aerobic capacity increased after supervised exercise and coaching, and the improvement was sustained during the one-year programme. However, no interactions between the group differences were seen, which suggests that repeated measurements could motivate to increased physical activity and thereby to increased aerobic capacity. As sub-max. VO2 increased over time, training-induced changes in VO2 on-kinetics could be another explanation. Little influence on HRQL was seen after the programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 73 publications
2
44
0
12
Order By: Relevance
“…Abrahão et al [5] found higher SF-36 scores in physical aspects and vitality, however, no significant differences were found in the score referring to the general health aspect. The same was reported by Boström et al [6], who after 12 months, concluded an improvement in the mental health field and considered it a positive effect, since there were lower feelings of nervousness and depression. However, regarding the general health aspect of QoL, no significant results were obtained.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Abrahão et al [5] found higher SF-36 scores in physical aspects and vitality, however, no significant differences were found in the score referring to the general health aspect. The same was reported by Boström et al [6], who after 12 months, concluded an improvement in the mental health field and considered it a positive effect, since there were lower feelings of nervousness and depression. However, regarding the general health aspect of QoL, no significant results were obtained.…”
Section: Discussionsupporting
confidence: 79%
“…In this meta-analysis, Abrahão et al [5] and Boström et al [6], performed a physical activity program during 03 and 12 months, respectively, including patients who have SLE in a physical activity program, and had control groups that received only usual care, was observed that there was a significant difference in relation to physical function (Fig. 4), but not to vitality (Fig.…”
Section: Physical Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…We cannot determine whether the improved mental function was a result of increased physical activity or frequent contact. Boström et al () conducted a 1‐year physical activity programme in women with SLE and found improvements in mental health at the sixth month. The same effect has been reported for other types of aerobic exercise training (Bogdanovic et al, ; Clarke‐Jenssen, Fredriksen, Lilleby, & Mengshoel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among those studies that have analysed the effects of physical activity on health-related quality of life (HR-QOL) among SLE populations, two studies show significant improvement in all areas of HR-QOL (Abrahão, Gomiero, Peccin, Grande, & Trevisani, 2016;Bogdanovic, Stojanovich, Djokovic, & Stanisavljevic, 2015). One study shows no improvement for any of the HR-QOL subscales except mental health (Boström et al, 2016).…”
Section: Introductionmentioning
confidence: 99%